Analisa Performansi Destilasi Air Laut Tenaga Surya Menggunakan Penyerap Radiasi Surya Tipe Bergelombang Berbahan Dasar Beton - Astawa, Ketut; Sucipta, Made; Artha Negara, I Putu Gede (Jurnal Energi Dan Manufaktur, 2012)
In principle, the distillation is a way to get clean water through desalination process dirty. In the refining processthere is a process of heat transfer, evaporation, and condensation. Heat transfer occurs from the heat source to the dirtywater. If water continues - it will happen again heated evaporation process. This steam on contact with cold surfaces it willbe a process of condensation on cold surfaces. In the distillation process condensate water is captured, germs and bacteriawill die by the heating process, and dirt will settle to the bottom basin One can use the sun's energy.In the system of solar distillation of sea water, absorber plate very important role because it serves as an absorberof solar radiation and convert light into heat energy that will heat the sea water above it. Based on the initial hypothesis ofthe authors that the type of flat-plate absorber is less than optimal, I will attempt to create a design and compare theperformance of sea water distillation appliance that uses a flat type absorber, absorber types of wavy, and wavy-coatedabsorbent type gravel. On the premise that type absorber has a broad corrugated heat absorption field is greater than theflat type absorber.Tests conducted from 09:00 am until 17:00 pm. The volume of sea water in the test as much as 30 liters. Testresults show the type of radiation absorber coated corrugated gravel produces more condensate is equal to 1295 grams withan average efficiency reaches 12.33%, and the type of radiation absorbent corrugated produce condensate for 1250 gramswith an average efficiency reaches 12.84% . While the radiation absorber can only produce a flat type of 795 ml with anaverage efficiency reaches 8.48%.
Keywords: Distillation, Solar, Wave absorbers Radiation Type